Solubility prediction of L-ascorbic acid by using COSMO-RS - Hassan, Syajaratul Jahriah; Adam, Fatmawati; Abu Bakar, Mohd Rushdi (2014)
Pharmaceutical is a highly regulated industry based on its nature that involves human life. Every decision must be scientifically sound from the early stage in order to provide security and safety to the patient. Only 1 from 4000 synthesized drugs reach the market which cost about $800-900 million dollar within 8-12 years from discovery to market. Any method that could expedite the research development is highly needed to reduce the development time of newly designed drugs. COSMO-RS is a fast and efficient methodology for predicting the thermodynamic properties of fluids and liquid mixtures that use a statistical thermodynamics approach based on the results of quantum chemical methods (QM) (Klamt & Eckert, 2000). It is programmed based on interacting molecular surface charges. By using COSMO-RS, only melting point and heat of fusion Δh is needed to determine the long and crucial solubility test in any solvent.